If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -1 + 4m = -13 Reorder the terms: -1 + 2m + 4m = -13 Combine like terms: 2m + 4m = 6m -1 + 6m = -13 Solving -1 + 6m = -13 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 6m = -13 + 1 Combine like terms: -1 + 1 = 0 0 + 6m = -13 + 1 6m = -13 + 1 Combine like terms: -13 + 1 = -12 6m = -12 Divide each side by '6'. m = -2 Simplifying m = -2
| -13=5-13+3a | | 25s^4-9p^2=0 | | 5x-3(x-3)=-6-4x+7 | | 7n=2n-36 | | s=2*3.14r*r | | 7(13x+9)+17x=-8x+18 | | 8(w+17)= | | 4=2.5g | | 5n-12=35 | | 1200x+250=3500 | | -5b+3=-72 | | q^2+6q+9-p^2=0 | | 7(13x+9)+17x=-8+18 | | 3.7x+47.4=16.4-11.8x | | 9g-10-14g=-3g+14 | | .5d-4=1 | | 9xm+-6=30 | | 6d-3d+2d=35 | | 5x-7m=4q | | 12.5=2g-(3.5) | | 3*1+d-5=3d-2 | | 1200x+250=1750 | | 7x-2=-3 | | 20z^2-8zx-45zx+18x*2=0 | | 10c-2=7c+4 | | y=7x^2+16x+4 | | 2(4-3t)-(-3)+2t= | | 8=8h+24 | | 2(3x+5)+x=-5x+9 | | (n)+(n+1)+(n+3)+(n+5)=216 | | 7x+2=-3 | | 3b^2-2b=8 |